1998
DOI: 10.1046/j.1365-2214.1998.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of care provided for children with epilepsy in the South Tees area

Abstract: This study examined the knowledge carers of children with epilepsy have of the condition and its management. It also examined their experience of medical services for their child and the attitude of staff at their schools. A school nursing sister using a semi-structured technique interviewed 48 carers of 53 children. A majority expressed dissatisfaction with outpatient medical care, especially that outpatient visits did not improve their knowledge of the condition or its treatment. Twenty-eight carers were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…14 Articles in school nurse publications commonly examine the impact of chronic diseases such as asthma, diabetes, epilepsy, and cancer on school-age children, with specific attention to the risks of frequent absenteeism. [15][16][17][18] A recent study suggests that compared with healthy children, more than twice as many adolescents with RAP miss more than 10 days of school per year. 19 Another study reports that children with RAP miss 3 times as many school days as their healthy peers.…”
Section: Discussionmentioning
confidence: 99%
“…14 Articles in school nurse publications commonly examine the impact of chronic diseases such as asthma, diabetes, epilepsy, and cancer on school-age children, with specific attention to the risks of frequent absenteeism. [15][16][17][18] A recent study suggests that compared with healthy children, more than twice as many adolescents with RAP miss more than 10 days of school per year. 19 Another study reports that children with RAP miss 3 times as many school days as their healthy peers.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete reporting or a skewed sample is possible explanations for this discrepancy. Previous studies have shown that it is not uncommon for a school to be unaware that an individual child has epilepsy (Hanai 1996; Stewart et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge, not coping with seizures, misinterpreting seizures or unnecessarily sending children home were examples of reasons given for dissatisfaction. Eighteen children were reported to have been denied certain school activities on account of their epilepsy (Stewart et al. 1998).…”
Section: Introductionmentioning
confidence: 99%
“…4 Siblings may miss out on school activities and face many disappointments, since activities in which the epileptic child may not participate may be terminated. 18,23 Coping strategies Previous South African studies in other research populations revealed significant positive correlations between avoidant coping strategies and anxiety as well as depression, in contrast with significant negative correlations between problem-solving coping strategies and anxiety as well as depression in parents of children with Down Syndrome 20 and in adults caring for depressed spouses. 26 In parents of children with epilepsy, effective problem-solving coping strategies as opposed to avoidant coping strategies should likewise help to diminish psychological distress.…”
Section: The Effect Of Childhood Epilepsy On Family Lifementioning
confidence: 97%
“…The family may spend less time enjoying activities outside the home, fearing that the child may have a seizure, and inviting friends to the home may come to an end. 18,23 One parent may have to end his/her employment outside the home to take care of the child, which may lead to a reduced income for the family and therefore the reduction of pleasurable activities. Having a child with epilepsy incurs many expenses, since specialist consultations, medication and special investigations are costly.…”
Section: The Effect Of Childhood Epilepsy On Family Lifementioning
confidence: 99%